Intravitreal Injection of Lucentis and the Vitreomacular Relationship in Patients with Exudative AMD: A Prospective Study - Mark T. Costen, Tahir Islam, Salina Siddiqui, Murtaza Mookhtiar, Louise M. Downey (Pakistan Journal of Ophthalmology, 2015)
Purpose: This study aimed to investigate the relationship between intravitreal injections of Lucentis and the vitreomacular surface. Material and Methods: Central macular thickness (CMT), LogMAR visual acuity and the presence or absence of posterior vitreous detachment (PVD) were noted in Lucentis eligible patients before commencing treatment, and 6 months after initial treatment prospectively. The paired sample t-test repeated measures ANOVA were used. Results: Of 52 eyes analyzed, 70% were noted to have no PVD prior to injection. Of these, 55% of eyes developed PVD. Comparison of the change in CMT between PVD-induced eyes and pre-existing PVD eyes was statistically significant. PVD induction during treatment was associated with a greater reduction in CMT than in eyes with pre-existing PVD. Conclusions: The induction of PVD may have an effect on CMT in eyes injected with Lucentis, implying a potential therapeutic effect of PVD in exudative AMD. Key words: Macular, Neovascularization, Age related macular degeneration, Lucentis